Work environment and work organization in the Swedish and Finnish mining industry - Johansson, Bo; Johansson, Jan (Luleå tekniska universitet, Arbetsvetenskap, 2008)
Godkänd; 2008; Bibliografisk uppgift: A baseline study of socio-economic effects of Northland Resources ore establishment in northern Sweden and Finland; 20090203 (biem)